Comparison of unilateral spinal anaesthesia using low dose bupivacaine with or without fentanyl in lower limb surgery - Jaiswal, Vinod S.; Thakare, Devendra W. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Intrathecal opioids are synergistic with local anesthetics and intensifies sensory block without increasing motor block. This combination makes it possible to achieve spinal anesthesia without hemodynamic instability and adverse effects that are associated with higher doses of bupivacaine. Hence we conducted this comparative study using 5 mg of hyperbaric bupivacaine with or without fentanyl (25 µg) in unilateral spinal anaesthesia for lower limb surgery. Methods: Sixty patients were randomized into two groups with Group B receiving 0.5% bupivacaine and Group BF receiving 0.5% bupivacaine + 25 µg fentanyl intrathecal. Sensory and motor block quality and duration, post anesthesia care unit stay (PACU) and adverse effects were compared. Results: The onset of sensory block (6.17±1.44) was faster in Group B compared Group BF (6.73±1.52) and duration of sensory blockade was intensified by addition of intrathecal fentanyl in Group BF. The onset and duration of motor blockade was similar in both the groups and was not affected by addition of fentanyl in Group BF. The number and mean duration stay in PACU was found to be significantly higher in patients 24 [80%]; 30 minutes receiving fentanyl suggesting it prolonged duration of recovery. No patient in either group had hypotension, respiratory depression, sedation, nausea, vomiting, PDPH and TNS. Only 1 patient in each group experienced bradycardia and 4 patients in Group BF had mild pruritus. Conclusions: Unilateral spinal anaesthesia with 5 mg hyperbaric bupivacaine with 25 µg fentanyl is a better choice than 5 mg hyperbaric bupivacaine alone in short procedure of lower limb in orthopaedic surgery.